Mapping the Landscape of Environmental Taxation Studies with a Bibliometric Approach - Judijanto, Loso (West Science Accounting and Finance, 2024)
This study presents a comprehensive bibliometric analysis of environmental taxation research, aiming to map the thematic landscape, identify research trends, and highlight potential areas for future investigation. Utilizing VOSviewer, the analysis encompasses 980 papers published between 1983 and 2024, revealing key themes such as economic impacts, sustainable development, emission control, and policy optimization. Temporal trends indicate a growing emphasis on integrating innovation and sustainability into environmental tax policies. Potential research areas identified include optimizing tax rates, exploring behavioral responses, and addressing equity considerations. The co-authorship network analysis highlights influential authors and collaborative clusters, suggesting opportunities for enhancing interdisciplinary research. This study provides valuable insights for policymakers, academics, and practitioners aiming to design effective environmental tax policies that address global environmental challenges.